2022
DOI: 10.1371/journal.pone.0272704
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of childhood maltreatment in relation to psychopathic traits

Abstract: Psychopathy is a personality disorder characterized by a mix of traits belonging to four facets: affective (e.g., callous/lack of empathy), interpersonal (e.g., grandiosity), behavioral instability (e.g., impulsivity, poor behavioral controls), and social deviance (e.g., juvenile delinquency, criminal versatility). Several scholars have argued that early childhood maltreatment impacts the development of psychopathy, although views regarding its role in the four facets differ. We conducted a meta-analysis inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 121 publications
6
15
0
Order By: Relevance
“…Our study adds to this research, suggesting that psychopathy is an important individual difference variable that may influence engaging in a range of abusive acts toward intimate partners in the earliest intimate relationships. Psychopathic traits are also increasingly found to have links with early adversity (de Ruiter et al, 2022), which we also found in our data (Table 1). Early adversity can also affect perpetrating IPV (McKinney et al, 2009), but our findings showed that psychopathic traits were associated with the different forms of IPV in adolescents beyond these factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study adds to this research, suggesting that psychopathy is an important individual difference variable that may influence engaging in a range of abusive acts toward intimate partners in the earliest intimate relationships. Psychopathic traits are also increasingly found to have links with early adversity (de Ruiter et al, 2022), which we also found in our data (Table 1). Early adversity can also affect perpetrating IPV (McKinney et al, 2009), but our findings showed that psychopathic traits were associated with the different forms of IPV in adolescents beyond these factors.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the potential importance of these formative early relationships, few studies have examined how psychopathic traits relate to IPV in adolescent populations (Robertson et al, 2020). There is also a need to consider how the link between psychopathic traits and early adversity (de Ruiter et al, 2022) could play a role in fostering abusive relationships. Those who experience abuse and/or witness violence between parents in their early relationships may go on to perpetrate violence in their own relationships (McKinney et al, 2009; Whitfield et al, 2003)—a process described as the cycle of violence (Widom, 1989, 2017).…”
mentioning
confidence: 99%
“…To summarize, based on the findings of Zara et al (2023) and others (de Ruiter et al , 2022) that inform how psychopathy develops, poor early relationships seem to predict the development of psychopathy. But the question of why psychopathy develops – examining its possible adaptiveness – given these poor relationships is a different consideration, one that benefits from evolutionary theorizing.…”
Section: An Active Exploitation Function Of Psychopathymentioning
confidence: 96%
“…Many of these studies, including Zara et al (2023), show that environments constituted by adverse childhood experiences seem to be associated with higher levels of psychopathy (Baglivio et al , 2020; Farrington and Bergstrøm, 2021). Many of these findings point to the presence of negative relationships that result in higher rates of abuse and neglect (Boduszek et al , 2019; de Ruiter et al , 2022), whereas other findings suggest social and economic disadvantage including reduced resources and social opportunities (Bégin et al , 2021; Piotrowska et al , 2015). An important contribution Zara et al make is showing how early life adversity, including events occurring prenatally, may factor into psychopathy’s development.…”
Section: A Protective Function Of Psychopathy?mentioning
confidence: 99%
“…In young people, these include poorer educational outcomes (Fry et al, 2018;Smiley et al, 2021). Across all ages, increased risks of psychiatric symptoms and diagnoses, suicidal behaviours, and further violence have been reported (de Ruiter et al, 2022;Hailes et al, 2019;MacIsaac et al, 2017;Smith et al, 2020;Wright et al, 2019). It also leads to psychological effects on families and carers of victims, healthcare workers, and communityrelated harms.…”
mentioning
confidence: 99%